Use of Beef Semen on Dairy Farms: A Cross-Sectional Study on Attitudes of Farmer Toward Breeding Strategies - Pereira, Jessica Marcela Vieira; Bruno, Daniela; Marcondes, Marcos Inacio; Ferreira, Fernanda Carolina (Frontiers in Animal Science, 2022)
The use of beef semen on dairy cows has been increasing steadily since 2017. We aimed to describe dairy management practices towards the use of beef semen by surveying farmers in California, the largest U.S. dairy producer. In January 2020, we mailed a printed version of the beef semen use survey to 1,017 dairy producers in California, who also had the option to answer the survey online. The questionnaire consisted of 33 questions that were categorized into three sections: general herd information (n = 10), beef semen management (n = 17), and sexed dairy semen management (n = 6). The response rate was 13.9% (n = 141). Regression models were used to evaluate the associations between the dairy-beef crossbred sale price, use of beef semen, and use of sexed dairy semen versus herd characteristics.. The mean ± standard deviation herd size was 1,693 ± 1,311 milking cows. Most dairies (81%) reported using beef semen on dairy cows. Among respondents, 78% reported extra profit as the main advantage of using beef semen, followed by control of heifer inventory (69%), genetic improvement (37%), and other factors (8%). Most respondents (58%) started using beef semen in the past three years, and 34% of the respondents were breeding more than 30% of all eligible cows with beef semen. Angus semen was the most used (reported by 89% of the respondents), followed by Limousin (12%), Wagyu (10%), Charolais (7%), others (5%, Limflex, Stabilizer, and Hereford), and Simmental (4%). Reproductive performance was an important criterion to select cows to receive beef semen, and 45% of the respondents reported starting breeding cows with beef semen from the third breeding on, 18% on the fourth, and 21% on the fifth or greater breedings. The region of California (a proxy for type of production system), contract with a calf ranch, and the herd breed explained 76.7% of the observed variation in the day-old dairy beef crossbred calf price. Survey results demonstrated the widespread use of beef semen in dairies and the main breeding strategies adopted by dairy farmers.